Audit of Discharge Summary Completion: Identifying Barriers and Implementing Solutions to Improve Timeliness - Katie Kopala; Reenie Villeda; Gaurang Surti; Suman Ahmed; Jennifer Luu (BJPsych Open, 2025)
Aims: Discharge summaries are an essential part of patient care, ensuring that key medical information, including progress on the ward and treatment plans, is communicated to GPs and community teams. On functional old age psychiatry Wards 3 and 4 at The Mount, Leeds, ensuring timely completion of summaries is important for patient care and safety. The aim is to identify the key factors contributing to delays in writing and sending discharge summaries, providing guidance for implementing changes that support timely completion and help achieve the 7 day target.